An analysis of the state of green business in the South African retail sector - Christelis, Theodora Anita (Department of Environmental and Geographical Science, 2016)
'Green' business is claimed by some South African retailers even though they lack well-founded and integrated sustainable, social, and environmental commitments. This is because no standards of greening exist for retail in South Africa. The purpose of this study is to explore, 'What constitutes green retail in the South African supermarket sector?' This required investigation into the sustainability of the companies' green business processes, social component of sustainability, and the existing state of the green retail sector. The five dominant supermarkets were selected to answer a questionnaire based on different environmental variables and principles. Interviewee responses were supplemented with publicly available company reports and these were then critiqued by allocating a level of commitment to sustainability of companies' green business processes, social considerations of sustainability, and establishing the current state of the green retail sector. Results show that within business processes, sustainable procurement is becoming increasingly accounted for through eco-labels and enterprise development programs. Distribution processes assist in verifying green claims and production. Various international and local sustainability programs are used to validate green efforts in the lack of national standards. Best practice frameworks are being utilised in the absence of local green standards and where limited, some are creating their own innovative solutions. Sustainability is a core focus at an executive level to some to ensure full integration of sustainability. Retailers may not necessarily pursue trends, but they have similar pressures that are often variably addressed. Although retailers' attempts to green their operations may not be standardised, the retail industry in South African has almost privatised sustainability and socio-economic development as they have superseded legislation to contribute to society and transform communities. It is an opportunity for retailers to take responsibility for their operations and in doing so create innovative solutions that address South Africa's environmental and social issues, in spite of the lack of green standards and governmental regulation, and in doing so become leadership companies that are accountable to their consumer base.